Oncological Surgical Plan during the covid19 pandemic, an experience of human care. Ciudad Hospitalaria Dr. Enrique Tejera, year 2020. (Salud, Arte y Cuidado, 2024)
Early oncological surgery is a condition associated with patient survival, compliance with which depends on various factors, including accessibility to the health service, a factor affected by the contingency measures taken during the Covid19 pandemic. Hence, the general objective of the study was to determine the results of the oncological surgical plan carried out during the Covid19 pandemic, as an experience of human care at the Ciudad Hospitalaria "Enrique Tejera", in 2020. The research design was cross-sectional descriptive. It was determined that a total of 65 elective oncological surgeries were performed, with a predominance of staging surgeries for breast and cervical cancer, colostomy and hemicolectomy; most of the patients were in the ideal time between diagnosis and surgery. concluding that the plan constituted a contribution of human care to cancer patients, facilitating the overcoming of the limitations of accessibility to surgery during the pandemic.
Keywords: planning; pandemic; covid19; accessibility,; cuidado humano; oncology quirurgica